Incidências decolonias em Arlete Nogueira da Cruz: da autoria ao romance - BRITO, Deyse Gabriely Machado (2023)
When questioning the hegemonic paradigms of power that prevail in Brazilian society, it is noted how there are mechanisms of coloniality in national literary historiography, consequently, in the canon. Thus, this study aims to reflect to what extent the Maranhão writer Arlete Nogueira da Cruz (1936), as well as her novel Compasso Binário (1971), which denounces crimes experienced by women of color, fracture the colonial order, establishing a new tradition in Brazilian literature. In this way, under the social-anthropological sieve of the decolonial theory in confluence with literary studies, the general objective was established to carry out a study of the canonical structures that end up leaving the voices of female writers veiled, by highlighting the literate Arlete Nogueira, as well as the novel Compasso Binário, which denounces crimes experienced by women of color. In order to do so, quantitative research was carried out, by investigating the record in the main Brazilian and Maranhão literary historiographies, as the qualitative bias seeks answers to the derisory incidences of female performance, in addition to problematizing the recurrent colonizing that affect violence forms that cross the female bodies in Arlet's literary plot. Thus, the theoretical framework is based on scholars such as Quijano (2005), Lugones (2020) and Segato (2020), to address colonialities and decolonial feminism; and, Coelho (1991), Schmidth (2006), Dalcastagné (2015) to address female writing and representation, among other diverse researchers. In addition, newspapers from the national and Maranhão press were used, such as Tribuna da Imprensa, O Combate, O Fluminense etc. It was possible to conclude that despite the advances that grant that there is the writing performed by women, unfortunately, the system of coloniality ends up hindering the visibility of this. Thus, it was addressed in Arlete Nogueira da Cruz and in the novel Compasso Binário, which is part of a literary project that is decolonial, the obstacles that the modern misogynist world is destined to women, as well as the forms that they use to r-exist.